2020
DOI: 10.1182/blood.2019003990
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbial metabolite trimethylamine N-oxide aggravates GVHD by inducing M1 macrophage polarization in mice

Abstract: The diversity of human microbiome heralds the difference of impact that gut microbial metabolites exert on allogenic graft-versus-host disease (GVHD), even though short-chain fatty acids and indole were demonstrated to reduce its severity. In this study, we dissected the role of choline-metabolized trimethylamine N-oxide (TMAO) in GVHD process. Either TMAO or high choline diet enhanced allogenic GVH reaction, while the analog of choline, 3,3-dimethyl-1-butanol reversed TMAO-induced GVHD severity. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
155
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(163 citation statements)
references
References 55 publications
7
155
0
1
Order By: Relevance
“…88 Recently, it has been demonstrated that a soluble microbiome-derived metabolite, trimethylamine N-oxide (TMAO), can drive murine macrophage polarization in an NLRP3 inflammasome-dependent manner. 89 Innate lymphoid cells (ILCs) are a more recently discovered heterogenous innate immune cell population specialized in the rapid secretion of polarized cytokines and chemokines to combat infection and promote mucosal tissue repair. 90 ILCs have been categorized into three distinct types based on transcription factors and cytokine signatures.…”
Section: Interaction Between Microbiota and Immune System In Homeostasismentioning
confidence: 99%
“…88 Recently, it has been demonstrated that a soluble microbiome-derived metabolite, trimethylamine N-oxide (TMAO), can drive murine macrophage polarization in an NLRP3 inflammasome-dependent manner. 89 Innate lymphoid cells (ILCs) are a more recently discovered heterogenous innate immune cell population specialized in the rapid secretion of polarized cytokines and chemokines to combat infection and promote mucosal tissue repair. 90 ILCs have been categorized into three distinct types based on transcription factors and cytokine signatures.…”
Section: Interaction Between Microbiota and Immune System In Homeostasismentioning
confidence: 99%
“…Recently, a study from China reported that the gut microbial metabolite choline-metabolized trimethylamine N-oxide exacerbates GvHD by inducing M1 macrophage polarization, and the underlying mechanism also involves NLRP3 inflammasome activation [ 145 ]. Therefore, further understanding the activation mechanism of the inflammasome in different types of cells and their roles in GvHD will help to effectively prevent and treat GvHD in the clinic.…”
Section: Inflammasomes In Hematological Diseasesmentioning
confidence: 99%
“…Wu et al recently reported the role of choline-derived trimethylamine N-oxide (TMAO) in the HSCT context [ 16 ]. This metabolite is already well known to play an important role in vascular inflammation and endothelial dysfunction, contributing to the genesis of atherosclerosis and thrombosis [ 60 ].…”
Section: Amino Acid-derived Metabolitesmentioning
confidence: 99%
“…The main involved bacterial strains are Anaerococcus hydrogenalis , Clostridium asparagiforme , Clostridium hathewayi , Clostridium sporogenes , Edwardsiella tarda , Escherichia fergusonii , Proteus penneri and Providencia rettgeri [ 62 ]. Both TMAO and choline were found to be associated in mouse model with an enhanced allogeneic GvHD reaction [ 16 ]. Furthermore, the authors demonstrate that TMAO induces the expression of M1 macrophages and M1-like cytokines both in tissues and in bone marrow in an NLRP3-dependent fashion [ 16 , 63 ].…”
Section: Amino Acid-derived Metabolitesmentioning
confidence: 99%